Copper-catalyzed reductive borylations on water. Issue 27 (6th July 2017) - Tanaka, Chihiro; Nakamura, Kimiaki; Nishikata, Takashi
Abstract: In this paper, we established copper catalyzed reductive borylation of terminal alkynes and diboron on water in the presence of amine. Moderate conditions enabled selective borylations of vinyl-substituted phenylacetylenes to undergo the borylation at a CC triple bond. The Cu catalyst can be recycled for seven times. Graphical abstract: